2022
DOI: 10.1002/ppul.25989
|View full text |Cite
|
Sign up to set email alerts
|

Nasal nitric oxide May not differentiate primary ciliary dyskinesia from certain primary immunodeficiencies

Abstract: The diagnosis of primary ciliary dyskinesia (PCD) is made through a combination of clinical features supported by a panel of diagnostic tests. Our cases highlight the similarities in the clinical presentation of patients with the specific immunodeficiency activated phosphatidylinositol 3‐kinase delta syndrome 1 (or PIK3CD‐related disorder) and PCD. We highlight the importance of repeating nasal nitric oxide testing when PCD has not been confirmed by genetic or ciliary electron micrograph analysis in the settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…nNO levels can be transiently below the cutoff during acute viral respiratory infections, then normalize after infection resolution 15 . Patients with immunodeficiencies can also have intermittently below the cutoff nNO levels 23 . nNO values may also normalize overtime due to improvement in testing technique and with age, as discussed previously.…”
Section: Discussionmentioning
confidence: 88%
“…nNO levels can be transiently below the cutoff during acute viral respiratory infections, then normalize after infection resolution 15 . Patients with immunodeficiencies can also have intermittently below the cutoff nNO levels 23 . nNO values may also normalize overtime due to improvement in testing technique and with age, as discussed previously.…”
Section: Discussionmentioning
confidence: 88%
“…35,36 Recent guidelines recommend using nasal nitric oxide (nNO) as a diagnostic test for PCD in individuals with a compatible clinical history. 36 Saunders et al 37 Organ laterality abnormalities, including situs inversus and situs ambiguus, are present in approximately 50% of individuals with PCD 38 due to malfunction of nodal cilia that create signaling gradients during embryogenesis. 39 Wee et al 40 hypothesized that chest X-ray alone misses a significant number of organ laterality defects.…”
Section: Non-cf Bronchiectasis and Pcdmentioning
confidence: 99%
“…Recent guidelines recommend using nasal nitric oxide (nNO) as a diagnostic test for PCD in individuals with a compatible clinical history 36 . Saunders et al 37 reported low nNO in two children with immunodeficiency secondary to PIK3CD gene variants. As lung disease in such patients may resemble that of PCD, alternative diagnoses should remain in consideration for patients with decreased nNO until confirmation of PCD diagnosis by electron microscopy or genetic testing.…”
Section: Non‐cf Bronchiectasis and Pcdmentioning
confidence: 99%